Modelling mass balance of cadmium in paddy soils under long term control scenarios. Issue 8 (17th July 2018) - Feng, Wenli; Guo, Zhaohui; Peng, Chi; Xiao, Xiyuan; Shi, Lei; Han, Xiaoqing; Ran, Hongzhen
Abstract : A simple mass balance model was developed for the change of Cd content in soils under long-term control scenarios. Abstract : A simple mathematical model on the basis of the mass balance principle was developed to simulate the long-term changes of Cd in paddy soils. The model predicted the dynamics of cadmium concentration in soils under six alternative control scenarios, including rice straw incorporation into fields (A), removing straw from fields (B), irrigating paddies with groundwater (C), reducing atmospheric Cd deposition (D), liming (E), and integrating measures (F), which were used for Cd contaminated paddy fields in the central subtropical areas of China. The uncertainty of parameters was analyzed using Monte Carlo methods. Scenario simulation results showed that atmospheric deposition was the main external source of Cd, contributing 70% of the total inputs, and plant uptake was an important output pathway, responsible for 92% of the total outputs. Removing straw from fields was more effective than other single control scenarios, and integrating measures were more effective in lowering Cd concentration in contaminated paddy soils. The Cd concentration in soils can meet the critical value (0.3 mg kg −1 ) in a low-level Cd contaminated paddy field (0.68 mg kg −1 ) with integrating measures through 40 years of cultivation. In the same case, a high-level Cd contaminated field (1.48 mg kg −1 ) was converted to a low-level Cd contaminated field (0.54 mg kg −1 ). However, long term use of lime can increase the Cd concentration in paddy soils. Controllable factors that affected Cd accumulation in paddy soils were plant uptake factors, and the atmospheric deposition flux and irrigation water flux of Cd. Therefore, integrating measures including removing rice straw and preventing the emission of Cd into the atmosphere and irrigation water was the optimal approach to lower Cd concentration in contaminated paddy soils.